Synthesis And Characterization Of Rgo And Tio2/rgo Composite Via Spray Pyrolysis Technique For Photodetector Application - Anoud Saud A, Alshammari (2021)
Among all new carbon-based structures, graphene has drawn the most attention because of its superiority in terms of porosity, elasticity, conductivity, surface area and stability. Recently, more attention has turned to graphene oxide (GO) thin films due to their exceptional structure and electronic properties, which enables their use in the manufacture of organic solar cells, photonic devices and potential applications in energy production and storage. However, the various reductive chemical compounds (hydrazine, sodium borohydride, etc.) in the reduction process to achieve reduced graphene oxide (rGO) are toxic. In this study, firstly a facile and cost-effective approach to synthesize rGO thin film from GO water dispersion were proposed. The rGO thin films were synthesized on glass substrates by means of spray pyrolysis technique (SPT), under different substrate temperatures (50, 100, 150, 200, 250, and 300 °C). All the synthesizes samples were characterized by different techniques such as Raman spectroscopy, field emission scanning electron microscopy (FESEM), X-ray diffraction analysis (XRD), energy-dispersive X-ray (EDX) spectroscopy, and UV–Vis spectroscopy. The reduction of GO to rGO was found initiated after 100 °C, as confirmed by the decrease in oxygen element shown by the EDX. While the resistance of the thin films decreased (i.e. conductivity increases) with increase in temperature. Secondly, the effect of spray cycles was studied on the morphological, structural, and optical properties under numbers of spray cycles (i.e. 2 to 10). The optical analysis showed that the energy band gap of GO and rGO thin films were reduced from 4.2 to 3.27 eV as the spray cycles increased from 2 to 10, which confirms the effect of surface coating thickness on conductivity.